Accessing Anonymised Data from Ireland’s Maternal and Newborn Clinical Management System for Research Purposes [version 1; peer review: 2 approved] - Richard A. Greene; Gillian M. Maher; Joye McKernan; Fergus P. McCarthy; Ali S. Khashan (HRB Open Research)
Background Since 2016, maternity units across Ireland have been switching from paper clinical notes to an electronic health record called the Maternal and Newborn Clinical Management System (MN-CMS). Currently, four units have implemented the MN-CMS: Cork University Maternity Hospital (CUMH), University Hospital Kerry (UHK), Rotunda Hospital and National Maternity Hospital (NMH). The MN-CMS provides opportunity for new data-driven discovery to answer important research questions on maternal and child health. Aim Provide detailed information on how a request can be made to access anonymised MN-CMS data for research purposes, as well as current timelines involved from initial request to data access. Methods A request to collaborate should be made to the clinical lead within each maternity unit where data is being requested in the first instance. A detailed protocol and data collection sheet should be drafted and forwarded to the National Information Governance Group for approval. A Data Protection Impact Assessment should be completed, and permission to access data from each maternity unit must be applied for separately from each unit’s local Ethics Committee. Upon receipt of ethical approval, an application to the Local Information Governance Group must be submitted if requesting data from CUMH and/or UHK. Data can then be extracted and anonymised by the data manager at the respective unit and transferred securely to relevant project personnel. Results The timeline from initial request to data access can range from approximately 6-12 months, depending on number of maternity units from which data is being requested and number of variables being requested from each unit. Conclusions Accessing MN-CMS data for research can be a complex process. A national standardised process for managing the data is needed. This would allow a clear pathway to be developed for accessing data to facilitate new data-driven discovery in the area of maternal and child health.